Pengakuan Sosial dan Nilai Pluralitas dalam Komunikasi Seni Lintas Busana Kontemporer - Razali, Geofakta (Magister of Communication Science, Sahid University Jakarta., 2023)
This research is a conceptual study that produces an understanding of pluralism that can be obtained through the communication actors of cross-dressing artists. This representation has an effect on the acceptance and acknowledgment of the plurality point of view in creating an attitude of respect for differences. Using the concept of recognition from Axel Honneth which provides an overview of social relations built on intersubjective grammar that influences human insight about differences. The researcher uses a qualitative method with a critical methodology to the form of practical dialectics and the theory of cross-dressing art performers, starting from their appreciation of themselves, and their communication behavior and social actions for a moral acceptance that is not in the realm of relativism or absolutism, but on recognition. So that intolerance can be reduced through an attitude of respect for the existence of others.